Investigation and management of a raised serum ferritin - Cullis, Jonathan O.; Fitzsimons, Edward J.; Griffiths, William JH; Tsochatzis, Emmanouil; Thomas, D. Wayne (British journal of haematology, 2018)
Summary Serum ferritin level is one of the most commonly requested investigations in both primary and secondary care. Whilst low serum ferritin levels invariably indicate reduced iron stores, raised serum ferritin levels can be due to multiple different aetiologies, including iron overload, inflammation, liver or renal disease, malignancy, and the recently described metabolic syndrome. A key test in the further investigation of an unexpected raised serum ferritin is the serum transferrin saturation. This guideline reviews the investigation and management of a raised serum ferritin level. The investigation and management of genetic haemochromatosis is not dealt with however and is the subject of a separate guideline.